PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC SISWA KELAS VIII 5 MTsN KAMANG KABUPATEN AGAM - Fuzidri .; Harris Effendi Thahar; Abdurahman . (Bahasa, Sastra, dan Pembelajaran, 2014)
Abstract : This study aims to describe the process of improving students’ reading comprehension skills through CIRC of VIII.5 students of MTsN Kamang. This research is a classroom action research. The subjects were students of class VIII 5 MTsN Kamang academic year 2013/2014. The selection of the research subject was based on the result of the students’ reading comprehension that lower than the other class. The research was conducted in II cycles. Each cycle consist of four stages, namely planning, action, observation, and reflection. Data were obtained in the form of qualitative and quantitative data. Qualitative data were collected through observation and field notes. Further, quantitative data obtained through objective tests and questionnaire of students learning. Based on the result of this research, the use of CIRC in learning reading comprehension skills can improve students' reading comprehension skills. This improvement was seen in the findings of the research, the students' average score on the first cycle was 71.6 was in sufficient classification, and on the second cycle with an average score 8.2 was at a good classification. From the data found from both cycle, it can be concluded that CIRC can i mprove students’ reading comprehension. In addition, the implementation of CIRC make learning process more interesting, fun because the students can be active, independent, and creative. Kata kunci: keterampilan membaca pemahaman, model pembelajaran kooperatif, tipe Circ